Combined inguinal hernia in the elderly. Portraying the progression of hernia disease. (September 2016) - Amato, Giuseppe; Agrusa, Antonino; Rodolico, Vito; Puleio, Roberto; Di Buono, Giuseppe; Amodeo, Silvia; Gulotta, Eliana; Romano, Giorgio
Abstract: Introduction: Identification of a combined hernia is a common occurrence in the course of inguinal hernia repair. This type of protrusion disease seems to affect the elderly, in particular. Very few investigations have been carried out to ascertain the structural changes that occur in the groin affected by this clinical condition. Method: Analysis of intraoperative findings of combined inguinal hernias evidenced in the elderly, from the most recent 100 groin hernia repair procedures carried out by a single operator, represents the basis of the article. Protrusions that presumably represent the forerunner of this type of hernia were also analyzed: double ipsilateral inguinal hernias composed of a direct and an indirect protrusion. The gross anatomical, as well as histological, modifications occurring during the development of combined protrusions were also evaluated. Results: Combined hernia was the most frequent protrusion in patients over 65 years, accounting for 36% of the total in this patient group. In the same patient cohort, double inguinal hernia further involves 22% of elderly subjects. Macroscopically, progressive disruption of the inguinal back wall and degenerative reabsorption of the inferior epigastric vessels were evidenced. Histologically, inflammatory infiltrate, significant nerve and vascular injuries, along with severe muscle degeneration were recognized. Conclusions: The results seem to confirm that inguinal hernia is an unremitting progressive disease caused by chronic compressive structural damage. Combined hernias represent a frequent clinical condition in the elderly consequent to long-term degenerative damage. Therapy of combined protrusions must consider the impact of visceral vector forces.